The Integration of Technology in Arabic Language Instruction at the Madrasah Aliyah Level - Dasep Bayu Ahyar; Ilham Hilmi Salim; Naima Salem Alzletni (JURNAL IJ-ATL, 2026)
The integration of technology has become increasingly important in contemporary Arabic language education because it shapes how students access, process, and engage with learning materials. This study aimed to examine how technology is integrated into Arabic language instruction at the Madrasah Aliyah level, focusing on forms of implementation, pedagogical functions, and instructional challenges. The study employed a qualitative case study design involving six informants consisting of one vice principal, two Arabic language teachers, and three students. Data were collected through classroom observation, semi-structured interviews, and documentation, and analyzed using data condensation, reduction, display, and verification. The findings show three main patterns: digital administration through the PIESA application, limited classroom technology use mainly for presentation, and teachers’ digital literacy challenges in pedagogical application. The novelty of this study lies in examining technology integration as an institutional and instructional process. The findings suggest the need for sustained professional development and pedagogically oriented technology support.